Explaoring the efficacy of deliberate practice and memorisation skills in the process of Learning Debussy's L'lsle joyeuse : practice-led study - Rhoodie, Hester Sophia (University of Pretoria, 2019)
Dissertation (MMus)--University of Pretoria, 2019.